Transient Resistive Switching for Nonvolatile Memory Based on Water‐Soluble Cs4PbBr6 Perovskite Films. Issue 11 (15th September 2019) - Chen, Ruqi; Xu, Jun; Lao, Meimei; Liang, Zhiwei; Chen, Yukai; Zhong, Chujie; Huang, Linjun; Hao, Aize; Ismail, Muhammad
Abstract : All‐inorganic halide perovskite Cs4 PbBr6 thin films are synthesized at low temperature through a facile chemical deposition method. The deposited films are implemented as a dielectric and dissolvable layer with the Au/Cs4 PbBr6 /PEDOT:PSS/ITO configuration for transient memory electronic devices. The bipolar resistive switching phenomena, good switching cycling (endurance), and long data retention (10 4 s) are demonstrated on as‐grown nonvolatile memory device to evaluate its high stability, reliability, and reproducibility. The I–V relationship shows ohmic conduction behavior at the low‐resistance state, whereas space charge limited current mechanism is dominating at the high‐resistance state. The conductive filaments formation and rupture, accompanied by Br − vacancies in Cs4 PbBr6 layer, are employed to elucidate switching mechanism. More interestingly, the soluble insulation layer of the devices is quickly dissolved and the color of films transforms from yellow to white as fast as 2 s in deionized water, which exhibits good transient performance. Moreover, the electrical characteristics as well as optical properties vanish absolutely to further demonstrate the abovementioned transition after the memory devices dissolve in deionized water. This work offers a novel way to prepare disposable electronic memory devices by utilizing cheap perovskite‐based materials for transient electronics memory area as well as implantable electronics systems. Abstract : Transient nonvolatile resistive switching memory devices based on all‐inorganic halide perovskite Cs4 PbBr6 films are fabricated by a facile chemical deposition method. It is demonstrated that the devices exhibit good endurance, excellent data retention, good transient and quick dissolution performances, which have great potential in transient electronics memory area as well as implantable electronics system.